The Influence of Online Game Addiction on Student Personality Attitudes - Sulaiman, Bagus; Rahman, Arief Nur; Zamzami, Muhammad Azriel; Horokubun, Nada Desriani; Novasarah, Desy (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2023)
In light of the widespread use of online games for entertainment and the potential negative impact of addiction on personality attitudes, this study investigates the causal relationship between online game addiction and personality attitudes among students. Specifically, the research aims to explore the nature of changes in personality attitudes resulting from online game addiction. The study, conducted with 226 students from the Faculty of Communication and Multimedia Sciences, Mercu Buana University Yogyakarta, Class of 2021, employs a descriptive and causal research design through a quantitative approach. Data is collected using online game addiction questionnaires and attitude personality surveys distributed directly to students. The findings reveal a substantial 63.7% influence of online game addiction on the personality attitudes of these students, underscoring the need for a nuanced understanding of the impact of online gaming on individuals. While the remaining 36.3% is influenced by variables not studied, future research might delve into these aspects for a more comprehensive understanding. This study contributes valuable insights into the intricate relationship between online game addiction and personality attitudes, with potential implications for educational and psychological contexts.